Demon slayer = Kimetsu no yaiba. Volume 8, The strength of the hashira - Gotoge, Koyoharu, 1988-; Stan!, 1964- (Demon slayer, 2019)
"After dealing with several demonic enemies aboard the Infinity Train, Tanjiro, Zenitsu and Inosuke must face the demon spirit of the train itself! Even if they can stop the demon train, the minions of Muzan Kibutsuji are still out there and Tanjiro must continue to improve his strength and skills. Learning the secret of the Hikonami Kagura and Flame Breathing will give him a powerful new advantage."--Page 4 of cover